1988
DOI: 10.1007/bf02795450
|View full text |Cite
|
Sign up to set email alerts
|

Trace element content in fingernails and hair of a nonindustrialized US control population

Abstract: The concentrations of 17 elements in the nail and hair of 117 subjects from a nonindustrialized environment were determined by instrumental neutron activation analysis (INAA). A new method of statistical treatment that allows for more meaningful use of detection limit values was used to process the concentration data. Geometric means and standard errors are presented for each element, along with a summary of the effects of age, sex, and treatment on the concentration of each element. For nails, these data repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 12 publications
4
18
3
Order By: Relevance
“…Other researchers reported that there was no correlation between nails vs. hair for the levels of Ni [32], and no correlation for other metals including Co and Cr in hair and nails samples [35].…”
Section: Citationmentioning
confidence: 98%
“…Other researchers reported that there was no correlation between nails vs. hair for the levels of Ni [32], and no correlation for other metals including Co and Cr in hair and nails samples [35].…”
Section: Citationmentioning
confidence: 98%
“…Hair: ;nited States (Iyengar et al, 1991(Iyengar et al, , 1978Katz and Katz, 1992;Paschal et al, 1989;Vance et al, 1988;Tuthill, 1996). Italy (Perrone et al, 1996;Caroli et al, 1992Caroli et al, , 1994Piccini et al, 1996;Contiero and Folin, 1994).…”
Section: Introductionmentioning
confidence: 97%
“…Poland (GlenH -Haduch et al, 1997;Owczarczak, 1988;Struz ak WysokinH ska and Kot, 1987). Nails: ;nited States (Vance et al, 1988;Garland et al, 1993;Iyengar et al, 1978;Chaudhary et al, 1995). Germany (Wilhelm et al, 1994).…”
Section: Introductionmentioning
confidence: 98%
“…Organic elements are carbon, sulfur and nitrogen, whereas inorganic elements are trace metals and electrolytes [6] . Most literature on elemental analysis of fingernails concerns trace elements [e.g., [7][8][9][10][11][12], whereas scarce literature refer to organic elements of fingernails. Available data consider nitrogen and sulfur content of fingernails in specific age groups like infants or in disease states [13][14][15][16][17][18][19][20][21] .…”
Section: Organic Elemental Composition Of Fingernailsmentioning
confidence: 99%